Determination of petrophysical parameters of reservoirs in promising horizons and formations of the Bulla-Deniz field based on integrated well data (using Techlog software) - K.A. Kerimova; U.Y. Samadli (Геофизический журнал, 2024)
The Bulla-Deniz field which is characterised by deep wells has not been fully explored despite its commissioning since 1975. Consequently, the intersection of the Productive Series (PS) deposits has been drilled to the top of the Kirmaky group. The deposits of the sub-Kirmaky and Gala formations have not been exposed in the field area. The Bulla-Deniz field is located in the northern portion of the oil-gas region of the Baku archipelago, which is part of the Azerbaijani sector of the Caspian Sea. The structure was investigated through a comprehensive geophysical exploration program which included mapping, structure-search and logging datas.